Cost-Effective Location Management for Mobile Agents on the Internet. (28th April 2015) - Chen, Chien-Sheng; Hwang, Jiing-Dong; Lu, Chyuan-Der; Yeh, Ting-Yuan
Abstract : Many mobile agent system-related services and applications require interacting with a mobile agent by passing messages. However, an agent's mobility raises several challenges in delivering messages to a mobile agent accurately. Consisting of tracking and message delivery phases, most mobile agent location management schemes create or receive many update messages and interaction messages to ensure the effectiveness of the schemes. In addition to downgrading the overall performance of a mobile agent location management scheme, excessive transmission of messages increases the network load. The migration locality of a mobile agent and the interaction rate between mobile agents significantly affect the performance of a mobile agent location management scheme with respect to location management cost. This work presents a novel Dual Home based Scheme (DHS) that can lower the location management costs in terms of migration locality and interaction rate. While the DHS scheme uniquely adopts dual home location management architecture, a selective update strategy based on that architecture is also designed for cost-effective location management of mobile agents. Moreover, DHS is compared with available schemes based on formulations and simulation experiments from the perspective of location management costs. Simulation results demonstrate that the proposed DHS scheme performs satisfactorily in terms of migration locality and interaction rate.